Restorasi mahkota jaket porselen fusi metal dan customed dowel pasca perawatan saluran akar satu kunjungan - Arisanti, Teleseptiserngi Dian; Mulyawati, Ema (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2016)
Porcelain fuse to metal restoration and customed dowel post one visit endodontic treatment. Esthetic of anterior teeth has an important role to build self-confidence. Common esthetic problem on anterior teeth is caries, causing damage to the crown and discoloration. The aim of the case report is to report a porcelain fuse to metal restoration and custom dowel post one visit endodontic treatment in the left central maxillary incisor. A 25-years-old male patient came to seek care of his discolorized left central maxillary incisor. The diagnosis has been established as followed, pulp necrosis with discoloration on left central maxillary incisor. Method : In this case, we have undergone the one visit endodontics treatment followed by porcelain-fused-to-metal crown restoration and custom dowel of the left central maxillary incisor. Result: Three months evaluation post treatment, the patient had no pain during chewing, traumatic occlusion, nor periodontal tissue issue. Conclusion: The restoration on anterior teeth and endodontic treatment can reestablished the function of the teeth moreover esthetic, increasing self-confidence